Meta-analysis: The Effectiveness of mHealth Mobile Application Use to Promote Physical Activity and Ideal Body Weight in Adult with Overweight - Farida Nur Aisyiyah; Bhisma Murti; Eti Poncorini Pamungkasari (Journal of Health Promotion and Behavior, 2022)
Background: Globally, overweight and obesity are significant contributors to morbidity and mortality, which in turn can reduce productivity and increase the burden of healthcare costs. Interventions to treat obesity include a comprehensive lifestyle approach (diet, physical activity, and behavioral therapy) to achieve and maintain weight loss. One method for monitoring weight loss program interventions is the use of a mobile health application (mHealth). This study aims to analyze the effectiveness of using mHealth on increasing physical activity and losing weight.Subjects and Method: This research is a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2011 and 2021 using databases from PubMed, Google Scholar and ScienceDirect. Based on the database, there were 15 articles that met the inclusion criteria. The analysis was carried out using the RevMan 5.3 . software.Results: Meta-analysis of 9 randomized controlled trial articles showed that overall mHealth increased physical activity by 0.19 compared to controls (SMD = 0.19; 95% CI= 0.06 to 0.32; p = 0.004). Higher intervention outcomes were obtained from interventions for more than 3 months (SMD = 0.31; 95% CI = 0.13 to 0.49; p < 0.001). Short-term effects for 3 months did not show significant results. A meta-analysis of 15 randomized controlled trial articles concluded that the use of mHealth overall was able to reduce body weight by 0.34 compared with no use of the mHealth application (SMD = -0.34; 95% CI = -0.52 to -0.17; p< 0.001). Higher intervention outcomes were obtained from the 6-month intervention (SMD= -0.52; 95% CI= -0.82 to -0.22; p < 0.001). Short-term effects for 3 months did not show significant results.Conclusion: Long-term use of the mHealth app is effective for increasing physical activity and losing weight in overweight adults. However, the effect of short-term intervention for 3 months has not shown significant result..Keywords: mHealth, weight loss, physical activity.Correspondence:Farida Nur Aisyiyah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: faridanur88@gmail.com. Mobile: +62 852-1493-3173. Journal of Health Promotion and Behavior, (2022), 07(03): 208-224DOI: https://doi.org/10.26911/thejhpb.2022.07.03.04